Extractable organic compound in smoke paticulate from burning of three tropical wood species - Tan, Hock Seng (Terengganu: Universiti Malaysia Terengganu, 2013)
Characterization of extractable organic compounds focusing on n-alkane and polycyclic aromatic hydrocarbon (PAH) in fresh waxes and smoke particulate matter from three tropical wood species viz. Rhizophora apiculata (RA), Melaleuca leucadendron (ML) and Hevea brasiliensis (HB) had been carried out. In addition, differences in distribution and concentration of n-alkane and PAH compounds in smoke particulate generated during three combustion stages (smoldering, flaming and charring) were also investigated.